Vpliv oddaljenosti bivanja na zaupanje v jedrsko elektrarno - Milan Simončič (Izzivi Prihodnosti, 2019)
Purpose and Originality: We are studying trust of external stakeholders in the nuclear facility.We want to prove that the different stakeholders the nuclear facility do not accept in the same way and that the distance of the place of residence has an important influence. According to public information, this is the first such research in Slovenia. It is particularly important because of long-term commitments to limit greenhouse emissions, ensuring a stable and competitive supply of electricity, where nuclear power plants can make a significant contribution to the solution. Method: We are studying the function of external stakeholders of nuclear power plant in correlation with confidence, including experience from other countries with nuclear power plants. The web survey includes important Slovene external stakeholders of the Krško nuclear power plant. In the analysis of the collected data we use descriptive and frequency statistics, Mann-Whinteyev and Kruskal-Wallis test. Results: The results of the research show that confidence in the nuclear object, measured by five variables, is in correlation with the distance from the nuclear power plant. The distance is expressed in two ways: firstly, we are confronting the local community of Posavje (living with the nuclear power plant) with other local communities in Slovenia, and secondly, for six different groups of external stakeholders we take into account the actual distance of the residence from the nuclear facility. Trust in a nuclear facility is greater for residents living closer to the nuclear power plant. In the case of placement of a new nuclear power plant, the stakeholders in Posavje will be more inclined to make such a decision, while the non-negligible share of the participants has no opinion on this. Society:Proven facts will nuclear power plant take into account in optimization of strategy of involving various groups of external stakeholders.Various stakeholders who influence on the perspective of nuclear energy in Slovenia and influence public opinion will be use the results of the research as the starting point for the realization of their interests. Limitations / further research: We are aware of certain degree of uncertainty that could be influenced by the extent of the selected sample. Research also makes sense to focus on other factors that influence the confidence of external stakeholders in the nuclear power plant.